Elicitation of the prausnitz-kustner reaction by antiidiotypic antibodies. - Geha, R S (1982)
Rabbit antiidiotypic IgG directed against IgG F(ab')2 anti-tetanus toxoid (TT) antibodies ("idiotype") elicited a Prausnitz-Kustner reaction in normal skin sites sensitized 48 h earlier with the serum of the idiotype donor that contained IgE anti-TT antibodies. The serum moiety that caused the sensitization was heat sensitive (56 degrees C, 1 h), and was specifically removed by passage over immunosorbents containing rabbit antihuman IgE or TT antigen. The data obtained indicate that human IgG and IgE antibodies share idiotypic determinants and raise the possibility that idiotypic interactions may play a role in the regulation of the IgE antibody response in man.